Małe obszary w koncepcji rozwoju regionalnego - Ponikowski, Henryk (Small Areas in Concept of Regional Development, 2008)
In the global economy processes of development are strictly positioned. This means that they have their source on definite small areas. We presuppose that these small areas fulfill regional space which create the basis for regional development. However, some of them are able to participate in processes of development. As the result concept of small areas assumes local generating of regional development. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 189-196